2005
DOI: 10.1089/bsp.2005.3.119
|View full text |Cite
|
Sign up to set email alerts
|

Remediation ofBacillus anthracisContamination in the U.S. Department of Justice Mail Facility

Abstract: The U.S. Department of Justice (DOJ) mail facility in Landover, Maryland, was contaminated with Bacillus anthracis spores as a result of the 2001 anthrax bioterrorism attacks through the U.S. postal system. Surface environmental sampling within the facility indicated that the contamination was due to receipt of mail that had come in contact with Bacillus anthracis spores from the source letters at the Brentwood postal facility in Washington, DC. The DOJ adopted a two-pronged approach for remediating the facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 4 publications
0
80
0
1
Order By: Relevance
“…Furthermore, aqueous ClO 2 is commonly used for the treatment of drinking water and for the control of mold in libraries (Southwell, 2002;WeaverMeyers et al, 1998). Following the 9-11 attacks in the USA, ClO 2 gas was used to treat the Bacillus anthracis spores detected in certain government buildings and on the exterior of mail packages addressed to a small number of government institutions (EPA, 2006;Canter et al, 2005). Finally, various studies have demonstrated the efficiency of ClO 2 in deactivating Bacillus endospores (surrogates for B. anthracis spores) (Buttner et al, 2001;Cortezzo et al, 2004;Young and Setlow, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aqueous ClO 2 is commonly used for the treatment of drinking water and for the control of mold in libraries (Southwell, 2002;WeaverMeyers et al, 1998). Following the 9-11 attacks in the USA, ClO 2 gas was used to treat the Bacillus anthracis spores detected in certain government buildings and on the exterior of mail packages addressed to a small number of government institutions (EPA, 2006;Canter et al, 2005). Finally, various studies have demonstrated the efficiency of ClO 2 in deactivating Bacillus endospores (surrogates for B. anthracis spores) (Buttner et al, 2001;Cortezzo et al, 2004;Young and Setlow, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This was used to decontaminate mail sorting machines. Paraformaldehyde has been used in the past to decontaminate biosafety cabinets (Canter et al, 2005).…”
Section: Decontamination Methods: Othersmentioning
confidence: 99%
“…Aqueous ClO 2 was also used on used on nonporous surfaces in two mail sorting machines (Canter et al, 2005). The of Bacillus subtilis, and the fungus Penicillium citrinum.…”
Section: Chlorine Dioxide Gas Was Used In the Cleanup Of Building Intmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Under a crisis exemption from EPA, ClO 2 gas was used to treat Bacillus anthracis spores in 2001 and 2002 in contaminated buildings and the exterior of mail packages. 16,17 Additional studies have been completed on the efficiency of ClO 2 for inactivation of Bacillus endospores, as surrogates for B. anthracis spores. 18 -21 Wilson and associates 22 conducted a laboratory study investigating the effect of ClO 2 gas on the colonies of four fungal species (Chaetomium globosum, Cladosporium cladosporioides, Penicillium chrysogenum, and Stachybotrys chartarum), ascospores (C. globosum), and mycotoxins produced by S. chartarum.…”
Section: Introductionmentioning
confidence: 99%